Studi In Silico Senyawa Bioaktif Daun Miana (Coleus scutellariodes (L). Benth) sebagai Inhibitor Enzim Asetikolineterase (Ache) pada Alzheimer: In Silico Study of Miana (Coleus scutellariodes (L). Benth) Leaf Compounds as Inhibitor Acetylcholinesterase (Ache) Enzyme in Alzheimer’s - Vitadella, Veronika; Bulan, Catherine Putri; Sinurat, Julius Alvin Novensius; Latief, Madyawati; Yusnaidar, Yusnaidar; Tarigan, Indra Lasmana (Jurnal Sains dan Kesehatan, 2024)
Abstract Alzheimer's contamination is a neurodegenerative sickness brought about by a decline in the blend of acetylcholine because of the breakdown of acetylcholine into choline and the determination of acidic corrosive by the compound Acetylcholinesterase (Hurt). Compounds known to have heartbeat restraining developments are promising medications for the treatment of these contaminations. In this investigation, in-silico studies were done on the blend found in Miana (Coleus) further to see whether this combination could be utilized as a remedial application in the treatment of Alzheimer's illness utilizing sub-nuclear docking procedures. From the consequences of the examination, it is realized that the Pyrazolopyridine compound is the best medication contender with a limiting energy and stable limitation benefit of - 6.96 kcal/mol and 7.95 µm separately, with hydrogen securities happening in the destructive development of amino SER 293.   Keywords:          Alzheimer’s; In Silico; Miana   Abstrak Penyakit Alzheimer adalah infeksi neurodegenerative, dan terjadi karena menurunnya kombinasi asetilkolin dampak dari penguraian asetilkolin menjadi kolin dan derivasi asam asetat oleh senyawa Asetilkolinesterase (Hurt). Larutan yang diketahui memiliki gerakan penghambatan denyut merupakan obat yang menjanjikan untuk pengobatan infeksi ini. Dalam eksplorasi ini, studi in-silico dilakukan pada campuran yang ditemukan di Miana (Coleus) selanjutnya untuk melihat apakah campuran ini dapat digunakan sebagai aplikasi pengobatan dalam pengobatan penyakit Alzheimer dengan menggunakan strategi docking sub-atomik. Dari hasil penyelidikan diketahui bahwa senyawa Pyrazolopyridine adalah pesaing obat terbaik dengan energi ikatan dan keuntungan stabil pengekangan masing-masing - 6,96 kkal/mol dan 7,95 µm, dengan ikatan hidrogen terjadi pada penumpukan korosif amino SER 293.   Kata Kunci:         Alzheimer’s; In Silico; Miana